2016
DOI: 10.1007/978-3-319-42085-1_38
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Students Media Usage

Abstract: Trends in media usage by students can affect the way they learn. Students demand the use of technology, thus institutions and instructors should meet students requests. This paper describes the results of a survey where drivers in the use of media show continuously increasing or decreasing values from the first to the fourth year of study experience at the Western University, Canada, highlighting trends in the usage of new and traditional media in higher education by students. The survey was used to gather dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…With 100 students in the first wave and 803 students in the second wave, they analysed the differences in technology use over the course of four years of study. The results indicated that, while overall the use of technology increased from first to the fourth-year students, the satisfaction with technology decreased (Gidion et al 2016).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…With 100 students in the first wave and 803 students in the second wave, they analysed the differences in technology use over the course of four years of study. The results indicated that, while overall the use of technology increased from first to the fourth-year students, the satisfaction with technology decreased (Gidion et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, for the international context, Gidion et al (2016) presented the results of a study regarding the use of new and traditional media of undergraduate HE students, for Western University in London, Ontario, Canada in 2012 and 2013. With 100 students in the first wave and 803 students in the second wave, they analysed the differences in technology use over the course of four years of study.…”
Section: Introductionmentioning
confidence: 99%
“…The report of NMC Horizon [3] shows that quick and all-round diffusion of digital media in the higher education leads to the changes in the academic student environment, and it also influences the study of their behaviour. In order to cope with the changing environment of education, the academic establishments must understand and analyze media behaviour of students [4]. Our research is devoted to the habits of use of social networks and messengers by students.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013-2014, the survey was administered at Western University to undergraduate students and faculty members (Gidion et al, 2016;Gidion et al, 2014a;Gidion et al, 2014b;Gidion et al, 2013). The instructor survey, which resembles the student questionnaire, intends to compare the media usage of students and instructors by examining possible divergences in media culture that may create problems in the use of media for studying and teaching.…”
Section: Introductionmentioning
confidence: 99%